RTHP-30. DOES THE TEMPORAL LOBECTOMY CAVITY NEED TO BE IRRADIATED? PATTERNS OF RECURRENCE AND IMPLICATIONS FOR POSTOPERATIVE RADIATION TREATMENT FIELD DESIGN FOR TEMPORAL LOBE GLIOMAS. (11th November 2019) - Teyateeti, Achiraya; Geno, Connie; Brown, Paul; Jethwa, Krishan; Stafford, Scott; Laack, Nadia; Mahajan, Anita; Yan, Elizabeth; Parney, Ian; Merrell, Kenneth
Abstract: BACKGROUND: Treatment of temporal lobe glioma (TLG) frequently includes partial or complete temporal lobectomy (TL) followed by radiotherapy (RT). However, there are two approaches for temporal resection cavity RT, 1) standard target volumes (STV) targeting the entire TL resection cavity, dura, and peri-tumoral brain parenchyma or 2) modified target volumes (MTV) targeting only the adjacent peri-tumoral brain parenchyma. We report patterns of failure and a dosimetric comparison of these approaches. MATERIALS AND METHODS: This was a retrospective review of 49 patients with WHO grade II-IV TLG who underwent partial or complete TL and post-operative RT between 1998 and 2018. Progression-free survival (PFS) was estimated using the Kaplan-Meier method. RESULTS: The median patient age was 56 years (range, 21–76). Patients were diagnosed with glioblastoma (n=32, 65%), anaplastic glioma (n=10, 20%) and low-grade glioma (n=7, 14%). Treatment included partial TL with STV (n=33, 67%), partial TL with MTV (n=5, 10%), complete TL with STV (n=8, 16%) and complete TL with MTV (n=3, 6%). Mean RT dose was 60 Gy (range, 40–76) in 30 fractions (range, 15–39). At median follow-up time of 18 months (range, 3–161), 44 patients (90%) experienced recurrence: 34 (77%) in-field, 5 (11%) out-of-field, and 5 (11%) both in- and out-of-field. Among the 39 in-field failures, the location of recurrence included brain parenchyma (n=38, 97%), ventricle (n=6, 15%), and dura (n=5, 13%). No patient experienced isolated dural recurrence regardless of tumor grade, extent of TL, or radiation volume. Median PFS was 20 months (95% confidence interval [CI]: 15–24). RT volume (STV vs. MTV) was not associated with worsened PFS (hazard ratio: 1.1, 95% CI: 0.5–2.6). MTV was associated with significant reductions in mean or max doses to brain stem, optic chiasm, optic nerves, hippocampus, and pituitary compared to STV. CONCLUSION: Omitting RT to the entire TL cavity may reduce dose to multiple normal tissues with no detriments in dural recurrence or PFS.